(untitled) (Педагогіка вищої та середньої школи, 2006)
The article is devoted to the analysts of functions of educational & creative activity and correlation of productive and reproductive components of cations. An author comes conclusion about wide potential of educational & creative activity for intellectually creative development of its subject.